Factors Related to Work Stress Among Inpatient Nurses at RSUD Mukomuko - Neka Puji Lestari; Wulandari Wulandari; Julius Habibi (Universitas Dehasen Bengkulu, 2026)
Background: The health service sector in hospitals, particularly the inpatient unit, is one where healthcare workers are vulnerable to work stress. If the majority of nurses experience work stress, it can disrupt the hospital's performance as they may not be able to provide optimal care. Objective: This study aims to identify the factors related to work stress among inpatient nurses at RSUD Mukomuko. Metods: he method used is an analytical survey with a cross-sectional research design. Data was collected through primary data by distributing questionnaires to 34 inpatient nurses at RSUD Mukomuko using Total Sampling technique. Data analysis was conducted using the Chi-Square test. Research results: Univariate analysis results show that more than half of the nurses (55.9%) have a short work period, more than half of the nurses (61.8%) have good interpersonal relationships, more than half of the nurses (67.6%) have a moderate workload, more than half of the nurses (52.9%) have poor sleep quality, and more than half of the nurses (61.8%) experience moderate work stress. Bivariate analysis results indicate a relationship between work period and work stress among nurses (p=0.007), a relationship between interpersonal relationships and work stress among nurses (p=0.005), a relationship between workload and work stress among nurses (p=0.024), and a relationship between sleep quality and work stress among nurses (p=0.017). Conclusion : The researchers recommend that the hospital management provide work assignments to nurses while considering various factors, including work period, work experience, and workload, so that nurses can deliver maximum service to patients without being burdened by personal issues arising from the existing work system in the hospital. Additionally, if possible, they should proportionally increase the number of nurses in accordance with the number of patients.